Methylene blue reduction test in semen analysis of White Pekin ducks - NAHAK, A K; GIRI, S C; MISHRA, P C; MOHANTY, D N; DASH, S K (The Indian Journal of Animal Sciences, 2014)
This study was undertaken to investigate the relationship between methylene-blue reduction time (MBRT) and other semen quality parameters in duck by analysis of correlation coefficients. Semen ejaculates (32), collected at 2 days interval from 10 randomly selected drakes, were examined for different seminal parameters like pH, volume, colour, mass activity, individual motility, livability, concentration, number of spermatozoa per ejaculate, total sperm abnormality per cent and MBRT. The overall mean time to decolourise methylene blue in the white Pekin ducks was 10.03±0.24 min with a range from 8 to 13 min. MBRT was negatively correlated with mean spermatozoa concentration, number of spermatozoa per ejaculation and colour of semen samples but positively correlated with individual motility and livability. High correlation of MBRT with seminal parameters indicated its practical utility in monitoring semen characteristics.